Cardiovascular Hypertensive Crisis: Recent Evidence and Review of the Literature - Varounis, Christos; Katsi, Vasiliki; Nihoyannopoulos, Petros; Lekakis, John; Tousoulis, Dimitris (Frontiers in Cardiovascular Medicine, 2017)
Despite the high prevalence of hypertension, only a small proportion of the hypertensive patients will ultimately develop hypertensive crisis. In fact, some patients with hypertensive crisis do not report a history of hypertension or previous use of anti-hypertensive medication. The majority of the patients with hypertensive crisis often report non-specific symptoms, whereas heart-related symptoms (dyspnea, chest pain, arrhythmias and syncope) are less common. Hypertensive crises can be divided into hypertensive emergencies or hypertensive urgencies according to the presence or absence of acute target organ damage, respectively. This differentiation is an extremely useful classification in clinical practice since a different management is needed which in turn has a significant effect on the morbidity and mortality of these patients. Therefore, it is very crucial for the physician in the emergency department to identify the hypertensive emergencies and to manage them through blood pressure lowering medications in order to avoid further target-organ damage or deterioration. The aim of this narrative review is to summarize the recent evidence in an effort to improve the awareness, recognition, risk stratification and treatment of hypertensive crisis in patients referred to the Emergency Department.